Penerapan Tari Persembahan Beras Kunyit dalam Kegiatan Ekstrakurikuler sebagai Upaya Pelestarian Tari Tradisional di MTsN Sarolangun - Okta Piana Putri; Afifah Asriati (SENDRATASIK UNP, 2023)
This article aims to describe the Application of Persembahan Beras Kunyit Dance in Extracurricular as an effort to preserve traditional dance in MTsN Sarolangun. This type of research is qualitative research with descriptive methods. The object of his research was the Persembahan Beras Kunyit Dance in extracurricular at MTs N Sarolangun. Types are primary data and secondary data. The data collection techniques used in this study are literature studies, observations, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of this study show that the application of turmeric rice offerings is applied through 4 stages, namely (1) implementation steps, (2) application planning, (3) implementation of application, (4) evaluation. The process of implementing the training was carried out as many as 6 meetings. Students have mastered the traditional dance dance skills of the Persembahan Beras Kunyit Dance offering well. Thus, this dance has been mastered by MTsN Sarolangun students, meaning that this dance has been preserved and the results of this application have been achieved as an effort to preserve the existing Sarolangun.